The level of fiscal transparency and accountability of budget users – evidence from Macedonia - Levkov, Nikola (Inderscience Publishers, 2016)
Research done in the past regarding the budget institutions and transparency/accountability issues was mainly focused on a national and local level. This is, to the best of our knowledge, the first study that evaluates transparency and accountability of budget users. The main contribution of this paper is in two areas: firstly, the level of transparency and accountability of budget users was evaluated using specially developed methodology; and secondly, the relationship between selected indicators and the level of transparency and accountability for budget users was analysed by using comparison of means and bivariate correlation. The results indicated that all monitored budget users have a very low level of transparency (on average 12.62%) and the average accountability of the budget users’ performance is almost five times higher than their average transparency (amounting to 64%). Another important result indicated that the size of the total budget is positively related to the level of transparency.Keywords: fiscal transparency; accountability; open government; budget user; performance of government; government efficiency; fiscal policy; budget systems; public policy; determinants of transparency; determinants of accountability; budget institutions.
Keywords: fiscal transparency; accountability; open government; budget user; performance of government; government efficiency; fiscal policy; budget systems; public policy; determinants of transparency; determinants of accountability; budget institutions.